The role of the immunoescape in colorectal cancer liver metastasis. - Chie Takasu (Public Library of Science (PLoS), 2021)
The expression of programmed death 1 (PD-1) and programmed death-ligand 1 (PD-L1) indicate the efficacy of anti-PD-1/PD-L1 therapy in colorectal cancer (CRC), but are less useful for monitoring the efficacy of therapy of CRC liver metastasis (CRLM). This study investigated the effects of immune molecules on the prognosis of CRLM. We enrolled 71 patients with CRLM who underwent curative resection for CRC. We used immunohistochemistry to analyze the expression of PD-1, PD-L1, indoleamine-pyrrole 2,3-dioxygenase (IDO), and CD163 (a marker of tumor-associated macrophages [TAMs]) in metastatic tumors. The immune molecules PD-1, PD-L1, IDO, and TAMs were expressed in 32.3%, 47.8%, 45.0%, and 47.9% of metastatic CRC samples, respectively. The 5-year overall survival rates associated with immune molecule-positive groups were significantly better than in the negative groups (PD-1: 87.7% vs 53.2%, p = 0.023; PD-L1: 82.4% vs 42.3%, p = 0.007; IDO: 80.7% vs 43.5%, p = 0.007; TAMs: 82.6% vs 48.0%, p = 0.005). Multivariate analysis revealed PD-1 expression (p = 0.032, hazard ratio: 0.19), IDO expression (p = 0.049, hazard ratio: 0.37), and tumor differentiation (p<0.001, hazard ratio: 0.02) as independent prognostic indicators. PD-1 and TAMs in metastases were associated with less aggressive features such as smaller tumors. Furthermore, TAMs positively and significantly correlated with PD-1 expression (p = 0.011), PD-L1 expression (p = 0.024), and tended to correlate with IDO expression (p = 0.078). PD-1, PD-L1, IDO, and TAMs in CRLM were associated with less aggressive features and better prognosis of patients with CRC, indicating adaptive antitumor immunity vs immune tolerance. These molecules may therefore serve as prognostic markers for CRLM.